Pengaruh Efektivitas dan Kontribusi Penerimaan Pajak Daerah terhadap Pendapatan Asli Daerah Kabupaten/Kota di Kalimantan Barat - Larasati, Anistya Fitri; Diaz, Marsela; Novieyana, Syarifah (Digital Business: Tren Bisnis Masa Depan, 2024)
This research aims to see the influence of the effectiveness and contribution value of regional tax revenues on the Regional Original Income (PAD) of districts and cities in West Kalimantan province during the Covid-19 pandemic. This research was conducted to test and analyze the relationship and correlation between the effectiveness of regional taxes and the contribution of regional taxes to local revenue for 14 districts and cities in West Kalimantan province. This type of research is associative research using data from district and city regional government financial reports in West Kalimantan province for 2020-2022. Researchers used Financial Report data for the last 3 years because an extraordinary event called Covid-19 occurred which affected local government income from taxes, levies and other income. Based on the results of simultaneous Hypothesis Testing for the variables Regional Tax Effectiveness (X1) and Regional Tax Contribution (X2) together they will influence the Original Regional Income of Regencies and Cities in West Kalimantan and the influence is 63.9%, while the remaining 36.1% is influenced by other factors outside this regression model.